Potencial impacto das mudanças climáticas nas perdas de solo e água na microbacia do córrego Jaqueira, Alegre - ES - Oliveira, João Paulo Bestete de (2010)
The control of erosion requires an understanding of the complex interactions between chemical, physical, hydrological and meteorological. Several mathematical models have been developed and improved in objective to predict the magnitude of soil loss by erosion, like the Water Erosion Prediction Project (WEPP). The potential of projected global climate changes to increase the risk of soil erosion, with related environmental consequences is clear, but the real damage is not yet known and needs to be evaluated. It was objectified with this work to evaluate the impact of climate change on soil loss and water catchment in the Espírito Santo. To reach the proposed objectives was held to characterize the watershed area of stream Jaqueira located in the Alegre-ES city, and the lifting of the input files of the WEPP model (climate, soil, land use and management and topography). Subsequently, we obtained the future climate scenarios through the deviations from expected values for the climatic elements (rainfall, solar radiation, maximum and minimum temperatures), according to the HadCM3 global climate model. Finally, we applied the model to predict soil loss and water through the integration of softwares GeoWEPP, TOPAZ and ArcView to current climatic conditions and relating to different time-slices (2020, 2050 and 2080) and emissions scenarios (A2 and B2). The obtained results allowed to conclude that: the current simulated average losses in the watershed of the stream Jaqueira are of 52.9 mm year-1 for the runoff and 17.5 t ha-1 yr-1; in the current scenario, the areas with the largest losses were secondary regeneration and natural grassland; the hillslope 3, by has average slope, land cover influences; is forecast in 2020 A2, B2 2020 B2 and 2050, increase the runoff and the rate of soil loss, when is expected increase in precipitation, is predicted by 2050 A2, 2080 A2 and B2 in 2080, reducing runoff and soil loss rate, even when expected increase in precipitation